Study on the micro-scale effect in the micro–nano organic pores of a shale reservoir. (February 2018) - Wu, Zisen; Dong, Pingchuan; Lei, Gang; Cao, Nai; Li, Yudan; Wang, Yifan; Zhang, Xuejiao
The micro-scale effect occurs because of the gas flows in shale reservoirs containing small organic pores. In this study, based on a lattice Boltzmann model incorporating the bounce-back and specular-reflection boundary conditions, the gas flow through two parallel plates driven by differential pressures is simulated, which in turn verifies the model. Considering the effects of the slippage, surface diffusion, and adsorption, the gas flow in the organic channels is simulated based on the proposed lattice Boltzmann model. It is shown that the micro-scale effect is significant in the gas flows in the micro-scale channels. The compression effect leads to a nonlinear distribution of pressures along the centreline of the flow channels, and the nonlinearity increases with an increase in the pressure difference between the two sides of the flow channel. In case of gas flows in organic pores, the adsorption effect decreases the free-gas velocities, and with a decrease in pore sizes, the average free-gas velocity is reduced owing to the increased adsorption effect. The slippage effect and surface diffusion have a significant impact on the free-gas velocity of the mass flow. Compared to the slippage effect, surface diffusion contributes more to the mass flow of gas in organic pores. An increase in the Knudsen number intensifies the slippage effect and surface diffusion and enhances the mass flow.